(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. La celebrazione del giorno del Signore - 2. L’ascendenza e lo sviluppo dell’obbligo - 3. Dalle origini del cristianesimo alle prime disposizioni canoniche - 4. La concezione del precetto nella canonistica classica - 5. Dalla disciplina tridentina alla codificazione piano benedettina - 6. L’attuale regolamentazione normativa - 7. La genesi dei canoni - 8. Il contenuto delle disposizioni codiciali - 9. Gli sviluppi e le indicazioni successive - 10. Il fondamento e la logica della partecipazione eucaristica - 11. La “sostanzialità” della prescrizione celebrativa - 12. L’incentivo e la riscoperta della pratica domenicale. The Foundation, Logic and Content of the Eucharistic Observance of the Precept Regarding Sundays and Holy Days of Obligation Abstract: This article examines the foundation and ratio of the eucharistic observance of the precept regarding Sundays and holy days of obligation, beginning with an overview of the question within both canonical tradition and current normative logic The historical-conceptual excursus highlights the maine phases of the formation of ecclesiastical discipline, while the analysis of current regulations demonstrates the continuity of normative provisions and eventual refinements. The dimension of justice manifests, above all, the social and institutional value of the precept, while the essential and particular characteristics of Christian holidays are also related to the communal and sacramental nature of the celebration. The logic behind the precept corresponds, then, to the solidarity, historicity, rationality and humanity of its observance. The regard for the “centrality of the Mass” leads to a respect for the substantiality and integrity of the good that is due. The incentive for and rediscovery of the Sunday practice depend primarily on catechetical and formative activity, but cannot be separated from juridical and directive contributions or the responsibility of members of the faithful and pastors.